PENGARUH MINUMAN JAHE TERHADAP EMESIS GRAVIDARUM - Antri Ariani (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Emesis gravidarum is a common complaint in early pregnancy. The occurrence of pregnancy causes hormonal changes in women due to an increase in the hormones estrogen, progesterone, and the release of human chorionic placenta gonadotropin. Emesis gravidarum during pregnancy can be overcome by non-pharmacological therapy, one of which is using ginger. This study aims to determine the effect of ginger on emesis gravidarum in first trimester pregnant women. The research design used was a quasi-experimental. The results showed that most pregnant women experienced emesis gravidarum in the first trimester of pregnancy and the study showed ginger as a non-pharmacological therapy that could affect the decrease in the frequency of emesis gravidarum in pregnant women. The conclusion is that there is an effect of giving ginger herbs to emesis gravidarum in pregnant women in the first trimester.